THE PROBLEM OF PERSONAL TRANSFORMATION IN DRAMATIC POEMS BY YURIY LYPA «THE BATTLE», «THE FEAST» - Атаманчук, В. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article outlines the concept of personal transformation and explores the features of his artistic embodiment in the dramatic works by YuriyLypa; genre peculiarities of literary works are determined; the mutual conditionality of content and form components isstudied; the forms of artistic conditionality used by the author are analyzed. Attention is paid to the definition of ontological elements of artistic and aesthetic constructions in the works «The Battle», «The Feast». The forms of artistic representation the notion of internal transformations due to essential changes are explored; ideas that constitute the content and form of YuriyLypaliterary works are defined. The key concepts that shape artistic integrity are outlined: the notion of worldview shifts in understanding the important aspects of being «The Battle»), the concept of illusory («The Feast»).